Clinicians' preferences for managing aneurysmal subarachnoid hemorrhage using endothelin receptor antagonists - Heidenreich, Sebastian; Trapali, Myrto; Krucien, Nicolas; Phillips-Beyer, Andrea (Frontiers in Neurology, 2023)
Background The endothelin receptor antagonist (ERA) clazosentan is being investigated for the medical prevention of cerebral vasospasm and associated complications, such as delayed cerebral ischemia (DCI), after aneurysmal subarachnoid hemorrhage (aSAH). This study quantified how clinicians weigh the benefits and risks of ERAs for DCI prevention to better understand their treatment needs and expectations. Methods An online choice experiment was conducted to elicit preferences of neurologists, intensivists, and neurosurgeons treating aSAH in the US and UK for the use of ERAs. The design of the choice experiment was informed by a feasibility assessment (N = 100), one-on-one interviews with clinicians (N = 10), a qualitative pilot (N = 13), and a quantitative pilot (N = 50). Selected treatment attributes included in the choice experiment were: one benefit (likelihood of DCI); and three risks (lung complications, hypotension, and anemia). In the choice experiment, clinicians repeatedly chose best and worst treatment options based on a scenario of a patient being treated in the ICU after aneurism repair. A correlated mixed logit model determined the relative attribute importance (RAI) and associated highest density interval (HDI) as well as acceptable benefit-risk trade-offs. Results The final choice experiment was completed by 350 clinicians (116 neurologists, 129 intensivists/intensive care clinicians, and 105 neurosurgeons; mean age, 47.4 years). Reducing the likelihood of DCI (RAI = 56.5% [HDI, 53.6–59.5%]) had the largest impact on clinicians' treatment choices, followed by avoiding the risks of lung complications (RAI = 29.6% [HDI, 27.1–32.3%]), hypotension (RAI = 9.2% [HDI, 7.5–10.8%]), and anemia (RAI = 4.7% [HDI, 3.7–5.8%]). Clinicians expected the likelihood of DCI to decrease by ≥8.1% for a 20% increase in the risk of lung complications, ≥2.4% for a 20% increase in the risk of hypotension, and ≥1.2% for a 20% increase in the risk of anemia. Conclusions Clinicians were willing to accept certain increased risks of adverse events for a reduced risk of DCI after aSAH. The likelihood of DCI occurring after aSAH can therefore be considered a clinically relevant endpoint in aSAH treatment development. Thus, evaluations of ERAs might focus on whether improvements (i.e., reductions) in the likelihood of DCI justify the risks of adverse events.